2012
DOI: 10.5014/ajot.2012.003582
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Evaluation of Social Interaction Measures Among People With and Without Neurologic or Psychiatric Disorders

Abstract: The ESI is sensitive with regard to detecting differences in quality of social interaction among groups expected to differ, suggesting that it is valid for use when the desired purpose is to identify people with diminished quality of social interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…The ESI demonstrates high inter-and intrarater reliability (r = .98). Parallel forms reliability among different types of social exchanges was r = .86, the many-facet Rasch equivalent of Cronbach's alpha was r = .93, and the mean standard error of ESI measures was 0.17 logit supporting high reliability (Fisher & Griswold, 2010;Søndergaard & Fisher, 2012). The ESI was administered during the baseline and probe phases in the present study.…”
Section: Evaluation Of Social Interaction (Esi)mentioning
confidence: 55%
“…The ESI demonstrates high inter-and intrarater reliability (r = .98). Parallel forms reliability among different types of social exchanges was r = .86, the many-facet Rasch equivalent of Cronbach's alpha was r = .93, and the mean standard error of ESI measures was 0.17 logit supporting high reliability (Fisher & Griswold, 2010;Søndergaard & Fisher, 2012). The ESI was administered during the baseline and probe phases in the present study.…”
Section: Evaluation Of Social Interaction (Esi)mentioning
confidence: 55%
“…Veterans expressed a desire to build on military experiences but did not talk about those military experiences with their peers. This incongruence between belief and behavior highlights a common problem student veterans have in relating to traditional-age students (Ackerman et al, 2009;DiRamio et al, 2008;Koenig et al, 2014;Tomar & Stoffel, 2014), a problem generally observed with interaction and participation as people engage in social interactions with others known and unknown to them (Søndergaard & Fisher, 2012). Veterans felt they did not have the social skills needed to relate to their peers, which is important because social skills influence successful engagement and participation in occupations (Doble, Bonnell, & Magill-Evans, 1991;Kopelowicz, Liberman, & Zarate, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Life Balance Inventory would provide a reliable and valid outcome measurement tool for such an occupation-based program (Matuska, 2012). • The prominent challenges veterans experience in social interactions highlight a performance skill practitioners can support for engagement in educational occupations (Simmons, Griswold, & Berg, 2010;Søndergaard & Fisher, 2012). Evaluation of social interaction outcomes (Fisher & Griswold, 2010) would provide an occupation-based outcome measurement for veterans in a natural context instead of a clinical setting.…”
Section: Implications For Occupationalmentioning
confidence: 99%
“…This result was partly expected for the investigated group of clients in rehabilitation to work and does not differ from previous findings when OSA has been used (24,25). Since there is some evidence showing that symptoms from a mental illness can contribute to limitations in social interaction (39), it was not expected that the item "Getting along with others" would be perceived as among the easiest to perform. One explanation of this could be related to how the item was interpreted by the clients, perhaps as a more general ability to find ways to get along with others without obvious problems.…”
Section: Discussionmentioning
confidence: 37%